A composite Gelatin/hyaluronic acid hydrogel as an ECM mimic for developing mesenchymal stem cell‐derived epithelial tissue patches. (2nd December 2019) - Kumar, Pramod; Ciftci, Sait; Barthes, Julien; Knopf‐Marques, Helena; Muller, Céline Blandine; Debry, Christian; Vrana, Nihal E.; Ghaemmaghami, Amir M.
Abstract: Here we report fabrication of Gelatin‐based biocomposite films and their application in developing epithelial patches. The films were loaded with an epithelial cell growth factor cocktail and used as an extracellular matrix mimic for in vitro regeneration of organized respiratory epithelium using Calu‐3 cell line and mesenchymal stem cells (MSCs). Our data show differentiation of Calu‐3 cells on composite films as evidenced by tight junction protein expression and barrier formation. The films also supported attachment, migration, and proliferation of alveolar basal epithelial cell line A549. We also show the suitability of the composite films as a biomimetic scaffold and growth factor delivery platform for differentiation of human MSCs to epithelial cells. MSCs differentiation to the epithelial lineage was confirmed by staining for epithelial and stem cell specific markers. Our data show that the MSCs acquire the epithelial characteristics after 2 weeks with significant reduction in vimentin, increase in pan cytokeratin expression, and morphological changes. However, despite the expression of epithelial lineage markers, these cells did not form fully functional tight junctions as evidenced by low expression of junctional protein ZO1. Further optimisation of culture conditions and growth factor cocktail is required to enhance tight junction formation in MSCs‐derived epithelial cells on the composite hydrogels. Nevertheless, our data clearly highlight the possibility of using MSCs in epithelial tissue engineering and the applicability of the composite hydrogels as transferrable extracellular matrix mimics and delivery platforms with potential applications in regenerative medicine and in vitro modelling of barrier tissues.